Electoral competition and endogenous political institutions: Quasi-experimental evidence from Germany - Thushyanthan Baskaran; Mariana Lopes da Fonseca (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
Do established parties change political institutions to disadvantage smaller, nonmainstream parties if the latters electoral prospects improve? We study this question with a natural experiment from the German federal state of Hesse. The experiment is the abolishment of an explicit electoral threshold (the so called "five percent hurdle") for local elections in 2001 by the Hessian state parliament. The abolishment improved the electoral prospects of smaller parties at local elections, but local politicians from large mainstream parties had the ability to adjust municipal political institutions in such a way as to counteract the increased competitiveness of smaller parties. One such institutional adjustment is to reduce the size of the local council and thereby raise implicit electoral thresholds. Using a dataset that covers all 426 Hessian municipalities over the period 1989-2011, we document with a difference-indiscontinuity design that municipalities where the electoral competitiveness of smaller parties improved more because of the abolishment of the explicit threshold, reduced their council size more. Hence, established parties appear to erect barriers to entry by adjusting political institutions once new political formations become viable electoral alternatives.
Keywords: D70; D72; D78; 330; electoral rules; electoral thresholds; political competition